Language, Migration, and Identity: Neighborhood Talk in Indonesia - Katharina Endriati Sukamto (Linguistik Indonesia, 2020)
Resensi BukuTitle : Language, Migration, and Identity: Neighborhood Talk in Indonesia ISBN : 978-0-521-51991-5, Hardback Author : Zane Goebel Publisher : Cambridge University Press, 2010, 241 pp.